Tratamiento quirúrgico de la incontinencia urinaria en el anciano. - Luengo Alpuente, S.; Mohamed Mohamed-abdallah, Z.; Ramírez Fernández, J.C.; Salinas Casado, J.; Begara Morillas, F. (Clínicas Urológicas de la Complutense, 1993)
Sin resumen